If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (X + 12)(x + 7) = 0 Reorder the terms: (12 + X)(x + 7) = 0 Reorder the terms: (12 + X)(7 + x) = 0 Multiply (12 + X) * (7 + x) (12(7 + x) + X(7 + x)) = 0 ((7 * 12 + x * 12) + X(7 + x)) = 0 ((84 + 12x) + X(7 + x)) = 0 (84 + 12x + (7 * X + x * X)) = 0 (84 + 12x + (7X + xX)) = 0 Reorder the terms: (84 + 7X + 12x + xX) = 0 (84 + 7X + 12x + xX) = 0 Solving 84 + 7X + 12x + xX = 0 Solving for variable 'X'. Move all terms containing X to the left, all other terms to the right. Add '-84' to each side of the equation. 84 + 7X + 12x + -84 + xX = 0 + -84 Reorder the terms: 84 + -84 + 7X + 12x + xX = 0 + -84 Combine like terms: 84 + -84 = 0 0 + 7X + 12x + xX = 0 + -84 7X + 12x + xX = 0 + -84 Combine like terms: 0 + -84 = -84 7X + 12x + xX = -84 Add '-12x' to each side of the equation. 7X + 12x + -12x + xX = -84 + -12x Combine like terms: 12x + -12x = 0 7X + 0 + xX = -84 + -12x 7X + xX = -84 + -12x Reorder the terms: 84 + 7X + 12x + xX = -84 + -12x + 84 + 12x Reorder the terms: 84 + 7X + 12x + xX = -84 + 84 + -12x + 12x Combine like terms: -84 + 84 = 0 84 + 7X + 12x + xX = 0 + -12x + 12x 84 + 7X + 12x + xX = -12x + 12x Combine like terms: -12x + 12x = 0 84 + 7X + 12x + xX = 0 The solution to this equation could not be determined.
| 0.50+0.10(3.00x+50.00)=1460 | | -(y-2)=-9y-30 | | x/40=1.43 | | 6(3x-6)=3(6x+5) | | 250x^4+128x=0 | | 10x^2=-3x+4 | | -2+2x=-4x+46 | | 7x+12=3x-5 | | s-10=7*(m-10) | | 12p-16p=12 | | 2x^2+3mx+10=0 | | 4x^3+5x^2-14x-9=0 | | (2x^3-(1/2)y)^6 | | -7+4x=-4x+33 | | 10u+20= | | F(x)=6logx+8 | | -7+6x= | | 8x-5(x-2)=16 | | y-2=5/4(x-2) | | 5(t-9)=15 | | 6a^2*5a^2= | | .75=1.5-3x | | -n+35n= | | 5(10x-1)+7=35x-4(5x+3) | | log(16)(8)=x | | 15*4%*1/12= | | -3/8(-6-24)=1/2(24-3-1 | | 3x=(x/3-10)*7 | | 1.025*18%*1/12= | | -7x-5y=82 | | y=3x^4-4x^3-12x^2+10 | | x^2+16x+54=6 |